A Review on Arshoghna Dravyas (Anti-Hemorrhoidal Drugs) of Dhanvantari Nighantu - Saini, Priyanka; Mishra, Rajesh Chandra (International Research Journal of Ayurveda & Yoga, 2024)
Medicinal plants, animal products, metals, and minerals have traditionally been a source of medicine in India through diverse systems of medicine such as Ayurveda. Ayurveda is one of the earliest forms of medicine. It prioritizes complete bodily health over disease management. Arsha are regarded as Piles (Hemorrhoids) in contemporary medicine. One typical anal-rectal issue is Piles. These are swollen and distended veins located around the rectum and anus. According to Ayurveda, the anus is called Gud and has three Valis (muscle folds) named Pravahini, Visarjani, and Savarini. Piles are seen in these three folds. A lot of medicines for the management of Piles have been described in Ayurvedic texts such as Charaka samhita, Sushruta samhita, Vagbhata samhita, and various types of nighantus. Dhanvantari nighantu is one of them and it is the oldest Ayurvedic materia medica which was compiled between 8th and 10th century A.D. The original name of this dictionary is Dravyavali samuchaya. Out of the total dravyas, 52 dravyas and certain types of oils and Sarvoushadi group of drug are described for the treatment of Piles in the entire treatise of Dhanvantari nighantu. This essay aims to concentrate on the data found in Dhanvantari nighantu about Arshoghna Dravyas.